Acid-Catalyzed Conversion of Cellulose Into Levulinic Acid With Biphasic Solvent System - Ma, Changyue; Cai, Bo; Zhang, Le; Feng, Junfeng; Pan, Hui (Frontiers in Plant Science, 2021)
In this work, acid-catalyzed conversion of cellulose into levulinic acid in a biphasic solvent system was developed. Compared to a series of catalysts investigated in this study, the Amberlyst-15 as a more efficient acid catalyst was used in the hydrolysis of cellulose and further dehydration of derived intermediates into levulinic acid. Besides, the mechanism of biphasic solvent system in the conversion of cellulose was studied in detail, and the results showed biphasic solvent system can promote the conversion of cellulose and suppress the polymerization of the by-products (such as lactic acid).The reaction conditions, such as temperature, time, and catalyst loading were changed to investigate the effect on the yield of levulinic acid. The results indicated that an appealing LA yield of 59.24% was achieved at 200°C and 180 min with a 2:1 ratio of Amberlyst-15 catalyst and cellulose in GVL/H2O under N2 pressure. The influence of different amounts of NaCl addition to this reaction was also investigated. This study provides an economical and environmental-friendly method for the acid-catalyzed conversion of cellulose and high yield of the value-added chemical.